Health Promotion Strategy Through Education of Drugs' Peril for Detainees in Relapse Prevention at National Narcotics Agency (BNN), East Kalimantan Province - Ferry Fadzlul Rahman; Kresna Febriyanto; Aisyah Nur Fadilah; Badrani Abbas Al-Fajri; Nisa Ardini; Rohana Rohana (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
Drug abuse is one of the problems that exist in Indonesia. The most case that occured in detainees in the BNNP Rutan is drug abuse case, so it is hoped that the prevalence of drugs can be reduced by providing education. The purpose of this activity was to increase the knowledge of prisoners about drug abuse and be able to understand ways to practice self-control to prevent drug abuse from happening again in prisoners. The method used in this activity was interviews and questionnaires to obtain problems. The results showed that the knowledge of prisoners about drug abuse increased after the counseling with p value 0.001 < 0.05 (alpha) with an average of 80 to 98. The conclusion of this activity was that it is hoped that prisoners can find out other ways of self-control that can be done while in detention to prevent relapse which is obtained based on their experience.